The Effectiveness of Think-Pair-Share Strategy on Improving Visually Impaired Students’ Speaking Skill at SLB-A Yapti Makassar - Rahmat J; Abidin Pammu; Ria Jubhari (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aimed to determine whether or not using the Think pair-share strategy could enhance students' speaking performance with visual impairments Grade XI of SLB-A Yapti Makassar in the academic year of 2020/ 202. This study was pre-experimental research in which the TPS strategy treated only one class. The data were qualitative and quantitative. The qualitative data were obtained by observing the teaching and learning process during the implementation of the TPS strategy and interviewing the students about this strategy. Meanwhile, the quantitative data were gained by assessing the students’ speaking skills through the pre-test and post-test. The instruments for collecting the data were the speaking rubric, observation guidelines, and interview guidelines. The results showed that the TPS strategy effectively improved the students’ speaking skills of visually impaired students. There are different significant scores on the speaking performance of students on pretest and posttest. The frequency and percentage of student scores in specific categories indicating post-test results are higher than pre-test results. Nonetheless, the TPS strategy also has the drawbacks where it was very time consuming during the implementation since students need to be dealt with the given lesson and the screen reader.